Kelps' Long-Distance Dispersal: Role of Ecological/Oceanographic Processes and Implications to Marine Forest Conservation - Batista, Manuela Bernardes; Anderson, Antonio Batista; Sanches, Paola Franzan; Polito, Paulo Simionatto; Lima Silveira, Thiago Cesar; Velez-Rubio, Gabriela M.; Scarabino, Fabrizio; Camacho, Olga; Schmitz, Caroline; Martinez, Ana; Ortega, Leonardo; Fabiano, Graciela; et al. (My University, 2018)
Long-distance dispersal is one of the main drivers structuring the distribution of marine biodiversity. This study reports the first occurrence of Macrocystis pyrifera and Durvillaea antarctica rafts on the southwestern warm temperate coast of the Atlantic Ocean. Our results indicate that an extreme meteo-oceanographic event, characterized by a northward, displacement of cold sub-Antarctic oceanic waters driven by an extratropical cyclone, could account for these unusual occurrences. A niche model based on known current distribution and maximum entropy principle (MAXENT), revealed the availability of suitable habitats at lower latitudes, outside their actual distribution edges. The distributional boundaries, mainly driven by temperature and irradiance, suggest the existence of environmental suitability in warm temperate areas, as well as in the Northern Hemisphere off Atlantic and Asian coasts. These theoretical edges and respective environmental drivers agree with the physiological affinities of both species, supporting the hypothesis that these variables act as limiting factors for their occurrences in tropical or warmer areas. Emerging regions can function as refuges and stepping-stones, providing substrate with adequate habitat conditions for recruitment of propagules, allowing eventual colonization. Long dispersal events reinforce the need for an extensive discussion on selective management of natural dispersion, biological invasions, refuge mapping and conservation initiatives in a transnational perspective.
Keywords: biogeography; extratropical cyclone; kelp rafts; marine migration; niche model; upwelling